Does Shared Decision Making Actually Occur in the Emergency Department? Looking at It from the Patients' Perspective. (26th September 2019) - Schoenfeld, Elizabeth M.; Probst, Marc A.; Quigley, Denise D.; St. Marie, Peter; Nayyar, Nikita; Sabbagh, Sarah H.; Beckford, Tanesha; Kanzaria, Hemal K.
Abstract: Objective: We sought to assess the frequency, content, and quality of shared decision making (SDM) in the emergency department (ED), from patients' perspectives. Methods: Utilizing a cross‐sectional, multisite approach, we administered an instrument, consisting of two validated SDM assessment tools—the CollaboRATE and the SDM‐Q‐9—and one newly developed tool to a sample of ED patients. Our primary outcome was the occurrence of SDM in the clinical encounter, as defined by participants giving "top‐box" scores on the CollaboRATE measure, and the ability of patients to identify the topic of their SDM conversation. Secondary outcomes included the content of the SDM conversations, as judged by patients, and whether patients were able to complete each of the two validated scales included in the instrument. Results: After exclusions, 285 participants from two sites completed the composite instrument. Just under half identified as female (47%) or as white (47%). Roughly half gave top‐box scores (i.e., indicating optimal SDM) on the CollaboRATE scale (49%). Less than half of the participants were able to indicate a decision they were involved in (44%), although those who did gave high scores for such conversations (73/100 via the SDM‐Q‐9 tool). The most frequently identified decisions discussed were admission versus discharge (19%), medication options (17%), and options for follow‐up care (15%). Conclusions: Fewer than half of ED patients surveyed reported they were involved in SDM. The most common decision for which SDM was used was around ED disposition (admission vs. discharge). When SDM was employed, patients generally rated the discussion highly.